La monosemia nel lessico di alta frequenza: un’indagine sull’italiano - Federica Casadei (Linguistik Online, 2023)
It has long been known in statistical linguistics that there is a strong correlation between the frequency of a word and its polysemy, i. e. that more frequent words tend to have more meanings. There are, however, also high-frequency words that are monosemous. The aim of this work is to investigate how many and which monosemous words are found in the Italian high-frequency lexicon, i. e. in the about 7,700 words that constitute the basic vocabulary (Nuovo Vocabolario di Base, NVdB). Confirming the relationship between frequency and polysemy, only 8% of the words in the NVdB are monosemous according to the main Italian dictionary, and a subsequent check in other dictionaries and in corpora further reduces the amount of monosemous words to less than 6%. A semantic analysis shows that the majority of them are technical or technical-like words with a very specific and referentially restricted meaning. (e. g. elettrone, stendibiancheria); but there are also words with a generic meaning (funzionamento), and non-referential words such as grammatical words (sebbene) or interjections (boh). These three classes of words could be considered more or less central cases of monosemy, adopting a prototype definition of this notion.